Human Properdin Opsonizes Nanoparticles and Triggers a Potent Pro-inflammatory Response by Macrophages without Involving Complement Activation - Kouser, Lubna; Paudyal, Basudev; Kaur, Anuvinder; Stenbeck, Gudrun; Jones, Lucy A.; Abozaid, Suhair M.; Stover, Cordula M.; Flahaut, Emmanuel; Sim, Robert B.; Kishore, Uday (Frontiers in Immunology, 2018)
Development of nanoparticles as tissue-specific drug delivery platforms can be considerably influenced by the complement system because of their inherent pro-inflammatory and tumorigenic consequences. The complement activation pathways, and its recognition subcomponents, can modulate clearance of the nanoparticles and subsequent inflammatory response, and thus alter the intended translational applications. Here, we report, for the first time, that human properdin, an up-regulator of the complement alternative pathway, can opsonise functionalised carbon nanotubes (CNTs) via its thrombospondin type I repeat (TSR) 4 and 5. Binding of properdin and TSR4+5 is likely to involve charge pattern/polarity recognition of the CNT surface since both carboxymethyl-cellulose (CMC-CNT) as well as oxidised (Ox-CNT) bound these proteins well. Properdin enhanced the uptake of CMC-CNTs by a macrophage cell line, THP-1, mounting a robust pro-inflammatory immune response, as revealed by qRT-PCR, multiplex cytokine array, and NF-κB nuclear translocation analyses. Properdin can be locally synthesized by immune cells in an inflammatory microenvironment, and thus, its interaction with nanoparticles is of considerable importance. In addition, recombinant TSR4+5 coated on the CMC-CNTs inhibited complement consumption by CMC-CNTs, suggesting that nanoparticles, decorated with TSR4+5, can be potentially used as a complement inhibitor in a number of pathological contexts arising due to exaggerated complement activation.